Penggunaan Biochar dan Dekomposer dalam Proses Pengomposan Limbah Kulit Buah Kakao serta Pengkayaan Mikrob Pelarut Fosfat (MPF) untuk Meningkatkan Kualitas Pupuk Organik: Application of Biochar and Decomposers to the Composting Process of Cocoa Husk and Enrichment Using Phosphate Solubilizing Microbe to Improve the Quality Organic Fertilizer - Haryanti Haryanti; Iswandi Anas; Dwi Andreas Santosa; Kurnia Dewi Sasmita (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2018)
The use of cocoa husk waste by farmers is not optimal. In general, farmers only dispose of or immerse cocoa husk waste without processing it into quality organic fertilizer. This study aims to determine the influence of biochar and decomposers in accelerating the process of composting cocoa husk waste and improving the quality of organic fertilizers, and the effect of adding Phosphate Solubilizing Bacteria (BPF) to organic fertilizer derived from cocoa husk waste on the growth of cocoa seedlings (Theobroma cacao L.). The first phase of the research was carried out a factorial 2 factor design in the Completely Randomized Design i.e. Biochar (without biochar and 10% biochar from the dry weight of organic fertilizer materials), and Decomposers (without decomposers and decomposers of 100 g kg-1 of organic fertilizer). The second phase of the study used a 3-factor factorial design in a Completely Randomized Design i.e. type of organic fertilizer (without organic fertilizer, organic fertilizer, organic fertilizer and biochar), inoculant Phosphate Solubilizing Bacteria (BPF), (without BPF inoculants, BPF A inoculants and BPF B inoculants), and dose of P fertilizer (without P fertilizer, SP-36 fertilizer 1 g P2O5, SP-36 fertilizer 2 g P2O5, and natural phosphate fertilizer 2 g P2O5). The results showed that the administration of biochar and decomposers did not accelerate the composting process. Provision of biochar and decomposers increases levels of humic acid. Giving natural phosphate 2 g P2O5 / 2.2 kg BKM increases the height growth of cocoa seedlings. Application of organic fertilizer with biochar or without biochar on the inoculant treatment factors of BPF A and BPF B significantly increased the diameter of the cocoa seedling stem. Application of organic fertilizer increases the stem diameter, plant height, number of leaves of cocoa seedlings, root dry weight and dry weight of stem of cocoa seedlings.